Pediatric venous thromboembolism: incidence and patient profile in a single Brazilian institution - Liana Ariel de Siqueira Lira; Jorge David Aivazoglou Carneiro; Maria do Carmo Menezes Bezerra Duarte (Hematology, Transfusion and Cell Therapy)
Background: As the diagnosis of Pediatric venous thromboembolism has dramatically increased in recent decades, this study aims to evaluate these patients, determining the incidence and describing their biological and clinical characteristics. Methods: An observational, cross-sectional study was conducted at a Brazilian quaternary hospital between January 2022 and February 2023. Under 18-year-old hospitalized patients with a confirmed diagnosis of venous thromboembolism were included, while those with arterial or chronic thrombosis were excluded. Data on biological and clinical characteristics, diagnosis and treatment were evaluated. A descriptive data analysis was performed and the incidence of hospital-associated thrombosis was calculated. Results: Thirty-nine pediatric patients were evaluated. The incidence of hospital-associated thrombosis was 19.9 cases per 10,000 pediatric hospitalizations. Median age at diagnosis was four months (range: 12 days-17 years). Most of the patients (66.7%) were asymptomatic, with venous thromboembolism being diagnosed incidentally. In all cases, at least one risk factor was identified and in 74.6% of cases four or more factors were present. The principal risk factors were the presence of a central venous catheter (89.7%) and infection (89.7%). Thrombogenic comorbidities, particularly congenital heart disease, were present in 48.7% of patients. Conclusions: The incidence of venous thromboembolism found in the present study was lower than rates reported in developed countries. The principal characteristics of this sample were a greater frequency of central venous catheter and infection as risk factors, and the fact that the cases consisted mainly of newborns and individuals with heart disease.